Improvements in Chronic Primary Insomnia after Exercise Training Are Correlated with Changes in Metabolic and Hormonal Profile. (15th April 2014) - de Souza Teixeira, Alexandre Abilio; Passos, Giselle Soares; Silva Ruiz, Francieli; da Silva Alves, Eduardo; Poyares, Dalva; Gonçalves de Santana, Marcos; Tufik, Sergio; de Mello, Marco Túlio
Abstract : Objective . The objective of this study was to correlate metabolic and hormonal parameters before and after 8, 16, and 24 weeks (wk) of moderate aerobic training in individuals with chronic primary insomnia. Method. Four male and sixteen female volunteers (adults, sedentary, and healthy) performed exercise training for 24 weeks. Blood and Pittsburgh Sleep Quality Index (PSQI) was obtained at baseline, 8, 16, and 24 wk of training. Results. PSQI scores decreased after 8, 16, and 24 wk of training regarding baseline values. Indeed, total sleep time (TST) increased after 16 and 24 wk of exercise training regarding baseline values. The correlations were analyzed using the delta (Δ ) values (Δ 1 = 8  wk less baseline;Δ 2 = 16  wk less baseline;Δ 3 = 24  wk less baseline). We have observed a negative correlation forΔ 1 between TST and cortisol, a positive correlation forΔ 3 between TST and growth hormone, a negative correlation forΔ 1 between TST and VLDL, a negative correlation forΔ 1 between TST and triacylglycerols, and a negative correlation forΔ 1 andΔ 2 between TST and thyroid-stimulating hormone. Conclusion. The exercise training improved the sleep quality of patients with chronic primary insomnia.